2021
DOI: 10.1007/978-981-15-9735-0_3
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Internet of Things for Personalized Healthcare: Study of Trends and Latent Research

Abstract: In this age of heterogeneous systems, diverse technologies are integrated to create application-specific solutions. The recent upsurge in acceptance of technologies such as cloud computing and ubiquitous Internet has cleared the path for Internet of Things (IoT). Moreover, the increasing Internet penetration with the rising use of mobile devices has inspired an era of technology that allows interfacing of physical objects and connecting them to Internet for developing applications serving a wide range of purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Research on SWS applied to diseases has shown an increased trend in recent years (see Figure 1 ). This is partially attributed to the marked progress in wearable sensors developments, which in turn is linked to progresses in embedded systems and material science [ 83 ], as well as the technological framework provided by Internet of Things (IoT), which facilitates data collection from mobile and wearable devices, apart from enhancing computing and storage capabilities through state-of-the-art technologies such as cloud computing [ 84 ]. However, the development of SWS applied to health is still an emerging field that has only been growing in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Research on SWS applied to diseases has shown an increased trend in recent years (see Figure 1 ). This is partially attributed to the marked progress in wearable sensors developments, which in turn is linked to progresses in embedded systems and material science [ 83 ], as well as the technological framework provided by Internet of Things (IoT), which facilitates data collection from mobile and wearable devices, apart from enhancing computing and storage capabilities through state-of-the-art technologies such as cloud computing [ 84 ]. However, the development of SWS applied to health is still an emerging field that has only been growing in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Current devices operating at the Things layer are not resilient, i. IoT-based healthcare network that is capable of observing and recording multiple types of health related data. After collecting data, different healthcare activities are performed such as monitoring, diagnosis, treatment, and remote surgeries [92]- [94]. In [95] the authors developed smart socks using textile-based triboelectric nanogenerator (TENG).…”
Section: A Things Layermentioning
confidence: 99%
“…One trend that has gained importance recently is moving from one size fits all in the field of medicine to Personalized Health Care (PHC) and medicine [ 6 , 7 ]. This happened due to the growth in aging population and the rise of the costs of chronic diseases.…”
Section: Introductionmentioning
confidence: 99%